DEREALIZATION DISORDERS IN EPILEPSY - P. N. Vlasov; A. V. Chervyakov; G. R. Drozzhina; M. V. Antonyuk; N. V. Orekhova; V. V. Gnezditsky; T. Yu. Noskova; P. A. Fedin (Эпилепсия и пароксизмальные состояния, 2016)
Derealization is mental disorder, manifested in a feeling of unreality and strangeness of the surrounding real world, a form of impairment of consciousness. The most common and recognizable such disorder is the phenomenon of «déjà vu» – deja vu (DV). Objective: to study the clinical and diagnostic value derealization disorders (DD) in epilepsy. Materials and Methods: the total study group was 152 persons (mean age 25,17±9,19; 63,2% of women). The phenomena of derealization were compared in groups of healthy subjects (n = 139) and patients with epilepsy (n = 23). Patients were interviewed on the DV characteristics and long-term (12-16 hours) ambulatory EEG monitoring was conducted. Results: the same frequency of DV in patients with cryptogenic and symptomatic focal epilepsy was demonstrated. DV could be combined with any types of seizures, it could be aura of a seizure or own seizure. The main clinical characteristics that differentiate DV in healthy from DV in patients with epilepsy are: frequency, fear of the onset DV and emotional coloring. The most important criterion is the dynamic characteristics of the DV: elongation increased the appearance of negative emotions. The DV phenomenon characterized in EEG by start with polyspiking activity in the right temporal leads and, in some cases, ended by slow wave, theta-delta activity in the right hemisphere